SPIRITUAL EDUCATION OF MARTIAL ARTS AS A SOLUTION TO REALIZE PEACE IN SOCIAL LIFE - Hartono, Djoko (http://jagadalimussirry.com/, 2019)
Empowerment of spiritual education aims to achieve peace in social life. The contradiction phenomenon is contrary to the intent and purpose of martial arts. The warriors began to indulge an arrogant passion that could cause chaos, commotion and even murder. The existence of martial arts is actually present to be aware of educating young people and Muslims in general to have faith, fear, be able to expose the curtain in the sheath of conscience until they find the pearl of heart enthroned, virtuous, reconcile of brotherhood and mamayu hayuning bawana. The spiritual education of martial arts needs to be returned, applied, and developed in human life, so that can realize the peace in social life.